Analyzing Elementary Teacher’s Understanding Towards Learning Instrument of 2013 Curriculum at SDN Sumbersari 1 Jember - Dimas A Haidar; Sitti A Hasanah; Fajar Surya Hutama (Pancaran Pendidikan, 2017)
The 2013 curriculum has been implemented starting from academic year 2013/2014 until now. In its implementation, the government has made various efforts to socialise the 2013 curriculum thoroughly, but with short preparations and learning instruments that are still in the perfection stage, it makes the low readiness of teachers. In fact, there are still many teachers who have difficulty in making and implementing curriculum learning instruments in 2013. Based on this case, this research is conducted to analyse the understanding of elementary school teachers toward the instrument of learning 2013 curriculum at SDN Sumbersari 1, Jember regency. The research method used is qualitative descriptive and the data collections are interviews, questionnaire, and observation. By the research which has been done, it can be indicated the teachers of SDN Sumbersari 1 find difficulty, especially in preparing lesson plan components,  instruments of effective assessment and student’s performance in a learning process. This can occur due to lack of training conducted by government and the instrument guidance is still not widely known by teachers